Ethanol metabolism modifies hepatic protein acylation in mice. - Kristofer S Fritz; Michelle F Green; Dennis R Petersen; Matthew D Hirschey (PLoS ONE, 2013)
Mitochondrial protein acetylation increases in response to chronic ethanol ingestion in mice, and is thought to reduce mitochondrial function and contribute to the pathogenesis of alcoholic liver disease. The mitochondrial deacetylase SIRT3 regulates the acetylation status of several mitochondrial proteins, including those involved in ethanol metabolism. The newly discovered desuccinylase activity of the mitochondrial sirtuin SIRT5 suggests that protein succinylation could be an important post-translational modification regulating mitochondrial metabolism. To assess the possible role of protein succinylation in ethanol metabolism, we surveyed hepatic sub-cellular protein fractions from mice fed a control or ethanol-supplemented diet for succinyl-lysine, as well as acetyl-, propionyl-, and butyryl-lysine post-translational modifications. We found mitochondrial protein propionylation increases, similar to mitochondrial protein acetylation. In contrast, mitochondrial protein succinylation is reduced. These mitochondrial protein modifications appear to be primarily driven by ethanol metabolism, and not by changes in mitochondrial sirtuin levels. Similar trends in acyl modifications were observed in the nucleus. However, comparatively fewer acyl modifications were observed in the cytoplasmic or the microsomal compartments, and were generally unchanged by ethanol metabolism. Using a mass spectrometry proteomics approach, we identified several candidate acetylated, propionylated, and succinylated proteins, which were enriched using antibodies against each modification. Additionally, we identified several acetyl and propionyl lysine residues on the same sites for a number of proteins and supports the idea of the overlapping nature of lysine-specific acylation. Thus, we show that novel post-translational modifications are present in hepatic mitochondrial, nuclear, cytoplasmic, and microsomal compartments and ethanol ingestion, and its associated metabolism, induce specific changes in these acyl modifications. These data suggest that protein acylation, beyond protein acetylation, contributes to the overall metabolic regulatory network and could play an important role in the pathogenesis of alcoholic liver disease.